2016
DOI: 10.1016/j.bbrc.2016.06.151
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid ameliorates glycemic control in diabetic mice via modulating pancreatic islet production of vascular endothelial growth factor-A

Abstract: Patients with type 1 diabetes mellitus are associated with impairment in vitamin A metabolism. This study evaluated whether treatment with retinoic acid, the biologically active metabolite of vitamin A, can ameliorate diabetes. All-trans retinoic acid (atRA) was used to treat streptozotocin (STZ)-induced diabetic mice which revealed atRA administration ameliorated blood glucose levels of diabetic mice. This hyperglycemic amelioration was accompanied by an increase in the amount of β cells co-expressed Pdx1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, native pancreatic islets are densely vascularized structures, in which CD31 and VEGF play a critical role in their vascularization and provide enough oxygenated blood for β-cells to maintain their normal mass and function to produce insulin of demand [41]. Also, studies on pancreatic tissues of both human diabetic patients [6] and experimental animals with induced DM including those with STZ model [42,43], have confirmed the vital role of CD31 and VEGF on islet vascularization, oxygenation, nourishment, survival, and insulin productivity [40,41,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, native pancreatic islets are densely vascularized structures, in which CD31 and VEGF play a critical role in their vascularization and provide enough oxygenated blood for β-cells to maintain their normal mass and function to produce insulin of demand [41]. Also, studies on pancreatic tissues of both human diabetic patients [6] and experimental animals with induced DM including those with STZ model [42,43], have confirmed the vital role of CD31 and VEGF on islet vascularization, oxygenation, nourishment, survival, and insulin productivity [40,41,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic β-cells, which produce insulin, become dysfunctional and dedifferentiate during diabetes progression [ 28 ]. RA signaling during endocrine specification appears to play a critical role in directing pancreatic endocrine cell fate and function [ 29 , 30 ]. Mice fed a VA-deficient diet for eight weeks had reduced β-cell mass, glucose-stimulated insulin secretion, and tissue VA levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In association with the RA-induced upregulation of RARβ, our studies demonstrated that at RA was capable of stimulating VEGF gene expression in amnion cells as has been demonstrated in other cell types. 24,25 Since the effect of at RA was not inhibited by cycloheximide, the stimulation of VEGF is most likely direct and not secondary through protein synthesis. This is further substantiated by identification of the RARE-DR5 sequence in the sheep VEGF promoter.…”
Section: Discussionmentioning
confidence: 99%
“…21 The RAR and RXR transcription factors are expressed in the placenta and regulate expression of placental genes 22 including placental lactogen and epidermal growth factor receptor. 23 In studies of retinal pigment cells 24 and pancreatic islet cells, 25 RA has been shown to modulate vascular angiogenesis and VEGF gene expression. More recently, the retinoid pathway has been described in human amniotic membranes and may be metabolically active to modulate amnion functions as has been shown for the AQP3 water channel.…”
Section: Introductionmentioning
confidence: 99%